The Fourth International Symposium on Genetic Disorders of the Ras/MAPK pathway. - Stevenson, DA; Schill, L; Schoyer, L; Andresen, BS; Bakker, A; Bayrak-Toydemir, P; Burkitt-Wright, E; Chatfield, K; Elefteriou, F; Elgersma, Y; Fisher, MJ; Franz, D; et al. (2016)
The RASopathies are a group of disorders due to variations of genes associated with the Ras/MAPK pathway. Some of the RASopathies include neurofibromatosis type 1 (NF1), Noonan syndrome, Noonan syndrome with multiple lentigines, cardiofaciocutaneous (CFC) syndrome, Costello syndrome, Legius syndrome, and capillary malformation-arteriovenous malformation (CM-AVM) syndrome. In combination, the RASopathies are a frequent group of genetic disorders. This report summarizes the proceedings of the 4th International Symposium on Genetic Disorders of the Ras/MAPK pathway and highlights gaps in the field. 2016 Wiley Periodicals, Inc.